(untitled) (The Pakistan Development Review, 1994)
This study examines the economic determinants of private foreign direct investment (FDI) by using a single-equation econometric model for 36 LDCs for the year 1983. The market size of the host country as measured by per capita GDP is found to be the most important factor in attracting FDI. The other important variables which influence FDI are found to be the cost factor (such as wage cost) and the investment climate in the host country (represented by such variables as per capita debt). The inflow of per capita public aid and economic instability, proxied by the volatility of prices, are other important factors affecting the flow of FDI. While larger market size and increased inflow of public aid attract FDI, the higher wage cost, poor investment climate, and economic instability in the host countries reduce the inflow of FDI. The model used to obtain these results is found to be structurally stable across countries.